EFFECT OF SHOPPING LIFESTYLE ON IMPULSIVE PURCHASE IN ONLINE STORE - Revi Sesario; Miftahorrozi Miftahorrozi; Aris Munandar; I Nyoman Tri Sutaguna; Muhammad Sulton Aminudin (Cross-Border Journal of Business Management, 2022)
The purpose of this study is to analyze effect of shopping lifestyle on impulsive purchase in Online Store. This research is a quantitative research with an associative approach. The types of data used in this study are primary and secondary data. The population in this study are consumers in Online Store for types of clothing in Medan City whose number is not known with certainty. The sample in this study were 145 respondents. Data analysis used simple regression analysis. The results show that shopping lifestyle has a positive and significant effect on impulsive purchase in Online Store for types of clothing in Medan City.